Hypothermic Shock Applied After Perinatal Asphyxia Prevents Retinal Damage in Rats - Rey-Funes, Manuel (Front Pharmacol, 2021)
Perinatal asphyxia (PA) can cause retinopathy and different degrees of visual loss, including total blindness. In a rat model of PA, we have previously shown a protective effect of hypothermia on the retina when applied simultaneously with the hypoxic insult. In the present work, we evaluated the possible protective effect of hypothermia on the retina of PA rats when applied immediately after delivery. Four experimental groups were studied: Rats born naturally as controls (CTL), animals that were exposed to PA for 20 min at 37°C (PA), animals exposed to PA for 20 min at 15°C (HYP), and animals that were exposed to PA for 20 min at 37°C and, immediately after birth, kept for 15 min at 8°C (HYP-PA). To evaluate the integrity of the visual pathway, animals were subjected to electroretinography at 45 days of age. Molecular (real time PCR) and histological (immunohistochemistry, immunofluorescence, TUNEL assay) techniques were applied to the eyes of all experimental groups collected at 6, 12, 24, and 48 h, and 6 days after birth. PA resulted in a significant reduction in the amplitude of the a- and b-wave and oscillatory potentials (OP) of the electroretinogram. All animals treated with hypothermia had a significant correction of the a-wave and OP, but the b-wave was fully corrected in the HYP group but only partially in the HYP-PA group. The number of TUNEL-positive cells increased sharply in the ganglion cell layer of the PA animals and this increase was significantly prevented by both hypothermia treatments. Expression of the cold-shock proteins, cold-inducible RNA binding protein (CIRP) and RNA binding motif protein 3 (RBM3), was undetectable in retinas of the CTL and PA groups, but they were highly expressed in ganglion neurons and cells of the inner nuclear layer of the HYP and HYP-PA groups. In conclusion, our results suggest that a post-partum hypothermic shock could represent a useful and affordable method to prevent asphyxia-related vision disabling sequelae.